1987
DOI: 10.1007/bf00044246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamine biosynthetic inhibitors on alkaloids and organogenesis in tobacco callus cultures

Abstract: We studied the effects of inhibitors of ornithine decarboxylase (ODC), arginine decarboxylase (ADC) and spermidine synthase (Spd synthase) on organogenesis and the titers of polyamines (PA) and alkaloids in tobacco calli. DL-alpha-diffluromethylarginine (DFMA) and D-arginine (D-Arg), both inhibitors of ADC activity, were more effective than DL-alpha-difluromethylorinithine (DFMO), an inhibitor of ODC, in reducing titers of PA and the putrescine (Put)-derived alkaloids (nornicotine and nicotine). Dicyclohexyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 32 publications
1
14
0
3
Order By: Relevance
“…These results may also imply the possibility of involvement of both ODC and ADC in PA synthesis as has been reported by Tiburcio et al (1987). Similarly, Berta et al (1997) found that thinning of cell walls of tobacco thin cell layer explants after DFMA and DFMO administration could be reversed by the supply of PAs.…”
Section: Discussionsupporting
confidence: 52%
“…These results may also imply the possibility of involvement of both ODC and ADC in PA synthesis as has been reported by Tiburcio et al (1987). Similarly, Berta et al (1997) found that thinning of cell walls of tobacco thin cell layer explants after DFMA and DFMO administration could be reversed by the supply of PAs.…”
Section: Discussionsupporting
confidence: 52%
“…Changes in PA levels have also been described during root formation in Phaseolus mungo [1], tobacco callus [12,25], corn [18] and apple seedlings [32]. Arginine (a precursor of Put) has been found to be involved in auxininduced root formation in Hibiscus cuttings [31], while exogenous Put was found to act synergistically with auxin in promoting root differentiation in Datura innoxia leaf explants [3].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous polyamine content varied during the rooting process, and different authors have proposed that they have a role in rhizogenesis (Hausman et al 1995a;Heloir et al 1996;Bellamine & Gaspar 1998;Arena et al 2003), but others do not support their participation in rooting (Tiburcio et al 1987;Biondi et al 1990;Jarvis et al 1983). Some workers have reported that adding polyamine can stimulate or even inhibit the rooting phenomenon depending on the polyamine type, concentration, and opportunity for their addition with regard to the different rooting phases (Martin-Tanguy & Carre 1993;Hausman et al 1995a;Sha Valli Khan et al 1999;Arena et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of polyamines in the culture media, and the removal of their effects through specific inhibitors, have already been proposed for several species (Tiburcio et al 1987;Hausman etal. 1994Hausman etal.…”
Section: Introductionmentioning
confidence: 99%